OPTIONS SPREAD TRADING STRATEGIES: LONG POSITION ANALYSIS - PUTRI NABILLA (NIM: 10112046), AMANDA
Options trading can involve more that one option called options spread. In trading, long position traders expect a relatively high return with low risk exposure. Optimal strike price and strike date to buy an options spread can be determined using a multi objective optimization method: Non-dominated Sorting Genetic Algorithm II which in this ﬁnal report is used to maximize mean yield rate and minimize CoVaR for each of ﬁve given options spreads. Three diﬀerent economic situations are assumed that by the end of optimiziation can be analyzed how each options spread reacts to the change of economy, and also the best options spread for each economic situation.